An Effective Feature Extraction through Fourgram Scheme for Long Payloads in Network Intrusion Detection Systems - Ali, Abdul Rustum; Rao, K N Brahmaji (International Journal of Computer Sciences and Engineering, 2025)
Now a day’s security is very global issue in Network based systems. The rate of cyber terrorism has increased day by day and it put national security under risk. In addition, network attacks have caused several damages to different sectors (i.e., individuals, economy, enterprises, organizations, and governments). Network Intrusion Detection Systems are giving the solutions against these attacks. NIDS always need to improve their performance in terms of increasing the accuracy and decreasing false alarm rates. Feature selection gives the ranking to the data set attributes and it can help for selecting the most important features from the entire set of data. In the previous researches feature selection selects the irrelevant and redundant features. These are causes of increasing the processing speed and time. An efficient feature selection method eliminates dimension of data and decrease redundancy and ambiguity. In the present network intrusion detection systems working with the long payload features are not easy tasks because many machine learning algorithms can’t handle these long payload features. Some of the Network Intrusion Detection Systems are not process these long payload features. To solve this problem, a new methodology called feature extraction through Fourgram technique has been proposed. The long payload features are processed these proposed technique and prepared to be implemented in machine learning algorithms and the results were carried out on ISCX 2012 data set. The designed feature selection system has shown a very good improvement on the performance using different metrics like Accuracy, F- Measure etc